Managing Labor Market Reforms: Case Study of Poland - Surdej, Aleksander (Washington, DC: World Bank, 2012)
When state socialism collapsed in Poland in 1989, Polish society hoped to rapidly establish well functioning democracy and efficient markets. This paper describes reforms to Poland's labor market, marked by a high unemployment rate, and labor market changes throughout the country's economic transformation. Labor law reforms were eased by the fact that the public opinion in Poland was favorable to deregulation; in part due to the perception that such changes would be advantageous to the society, and in part because no credible alternative existed. Polish mass media overwhelmingly supported labor law reforms and there were no voices calling for an alternative (for instance an interventionist approach) approach to try to reduce unemployment.